Examining the effects of mobility-based air and noise pollution on activity satisfaction. (December 2020) - Ma, Jing; Rao, Jingwen; Kwan, Mei-Po; Chai, Yanwei
Highlights: Activity satisfaction and air and noise pollution vary in space and time. Geographic contexts matter in activity satisfaction. Perceived environmental exposures are significant covariates of wellbeing. Perceived air pollution has a greater effect than noise on activity satisfaction. Abstract: Understanding how mobility-based real-time exposures to environmental pollution influence activity satisfaction has great potential for improving subjective wellbeing. Using real-time data from Global Positioning System trajectories and portable sensors collected in Beijing, this study investigates whether and how individual's real-time and perceived exposures to air and noise pollution at a fine spatio-temporal resolution influence activity satisfaction while controlling for geographic contexts, activity characteristics, socio-demographic attributes, health and life circumstances. The results show that activity satisfaction and air and noise pollution vary greatly in various microenvironments. Perceived air and noise pollution are more significant covariates of activity satisfaction than objectively measured pollution, and air pollution has a greater effect than noise pollution on activity satisfaction. These findings indicate that more granular data should be collected to further examine the relationships among geographic microenvironment, personal exposure and wellbeing, and compact city design is of great potential for improving subjective wellbeing.